Microbial endophytes : functional biology and applications - Kumar, Ajay, PhD; Radhakrishnan E. K (Woodhead Publishing is an imprint of Elsevier, 2020)
Microbial Endophytes: Functional Biology and Applications focuses on endophytic bacteria and fungi, including information on foundational endophytes and the latest advances in relevant genomics, proteomics and nanotechnological aspects. The book provides insights into the molecular aspects of plant endophytes and their interactions and applications, also exploring the potential commercialization of endophytic microorganisms and their use as bio fertilizers, in biocontrol, and as bioactive compounds for other sustainable applications. Coverage of important and emerging legal considerations relevant to those working to implement these important bacteria in production processes is also included. --